Measurement of Tidal Currents at Lituya Bay (Alaska): Introducing Aerial Photogrammetric Methods - Taylor, Charles B.; Harris, William D. (The International Hydrographic Review, 2018)
The U. S. Coast and Geodetic Survey made the first tidal-current observations at the entrance to Lituya Bay, Alaska, in the summer of 1959. Three methods of measurement were employed to determine the maximum flood and ebb currents and to determine their Greenwich time interval. (1) The Roberts radio current meter was used near the entrance, but out of the main current stream, to make a 100-hour record of the times of slack and maximum current for both flood and ebb tides; (2) Mast-bearing free floats were tracked through the narrow entrance by observers on opposite shores. The observations were made with sextants using radio to coordinate the reading times. This method was not satisfactory for either time or velocity determination; and (3) Free floats without masts were photographed with an aerial photogrammetric camera to obtain the best determination of the maximum surface-current velocity. The photogrammetric method is described in detail from the planning stages to the data reduction.